The Role of Emotional Intelligence and Conflict Management in Job Satisfaction and Teamwork: A Systematic Review - Ashenafi Woldemichael Woime; Goferie Adisho Shato (Public Health Challenges)
ABSTRACT This systematic review analyzes the roles of emotional intelligence (EI) and conflict management (CM) in promoting job satisfaction and teamwork within corporate settings. The study draws upon research from databases such as SAGE, Elsevier, APA PsycArticles, Wiley Online Library, and others, following a structured approach using Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines to identify, analyze, and synthesize relevant literature. The findings indicate that strong EI helps individuals identify, regulate, and express emotions effectively, fostering resilience against workplace stress and enhancing interpersonal interactions. Consequently, employees with higher EI report greater job satisfaction. Furthermore, effective CM approaches, supported by EI, facilitate constructive responses to workplace disagreements, thereby strengthening team cohesiveness and performance. The study highlights the universal relevance of EI and CM in creating a positive work environment, with key findings suggesting that organizations investing in EI training and leadership development can cultivate a more harmonious and productive workforce. Additionally, the interconnection between EI and CM emphasizes their combined impact on organizational performance, as emotionally intelligent leaders can effectively manage conflicts, transforming challenges into opportunities for growth. This article underscores the importance of integrating EI and CM frameworks into organizational strategies to enhance resilience, cooperation, and overall employee well‐being. The implications of this study are vital for business leaders, HR practitioners, and policymakers seeking to improve workplace satisfaction and team collaboration.